Case Report with Literature Review: Tumor-induced osteomalacia from a soft-tissue phosphaturic mesenchymal tumor of the trunk - Tao, Huiyuan; Deng, Zhimin; Chen, Li; Wang, Wenli; Zhou, Yuqing; Wu, Yue (Frontiers in Endocrinology, 2025)
BackgroundTumor-induced osteomalacia (TIO), a type of acquired hypophosphatemic osteomalacia, is brought on by tumors producing excessive levels of fibroblast growth factor 23, which raises renal phosphorus excretion.MethodsThrough a review of the literature, we have outlined the clinical characteristics of 33 patients with soft-tissue TIO of the trunk and described a case of TIO brought on by a soft-tissue tumor on the back.ResultsA 63-year-old woman who had been experiencing generalized bone pain for approximately three years visited the hospital. Physical examination revealed a round mass on the back measuring approximately 2 × 2 cm. Laboratory tests showed low blood phosphorus, elevated synchronous urinary phosphorus, and elevated alkaline phosphatase levels. The mass was detected using magnetic resonance imaging and ultrasound, and it was subsequently surgically excised. Following surgery, phosphate levels returned to normal, bone pain was relieved, and pathology confirmed phosphaturic mesenchymal tumor (PMT). A literature review identified only 33 cases of soft-tissue TIO occurring in the trunk, with a mean age of 49.7 ± 15.6 years and a male-to-female ratio of 23:10. Bone pain was present in 91% of patients, and diagnostic delay of more than two years was observed in 72.4% of cases. The mean preoperative serum phosphorus level was 0.48 ± 0.137 mmol/L, and the median tumor size was 3 cm (IQR: 2–4.65 cm). Postoperative remission of biochemical indices and clinical symptoms was observed in 96.9% of patients, with no recurrence during the follow-up period. The majority of tumors (72.7%) were pathologically diagnosed as PMT.ConclusionSoft-tissue TIO of the trunk is rare. Clinicians should be alert to the possibility of TIO in patients with unexplained bone pain and hypophosphatemia and should promptly perform appropriate examinations to avoid missed diagnoses.